Studies on the genetical properties of palmar and sole dermatoglyphics - Loesch , Danuta (Anthropological Review, 1975)
The paper presents the results of genetical analysis of dermatoglyphic characters, as classified by the new topological method, introduced by Penrose and Loesch. Firstly, the difficulties in genetical analysis of non-metrical dermatoglyphic characters and the limitations of the traditional classification methods in this respect, concerning particularly sole patterns, are pointed out. Then, the principles of the alternative method of classification are briefly explained. This method is based on the topological formula of Penrose [24] and includes only topologically significant pattern elements, which are the two complementary pattern types- loops and triradii, as shown in Fig. 1. Loops are classified according to the area in which they occur and to the direction of their cores, and arranged in an individual description of pattern in a numerical order; as to the triradii, the traditional nomenclature has been preserved as far as possible and, in an individual description, they are arranged in alphabetical order and follow the loops. All topologically significant pattern elements, as classified by the new method, are illustrated in Fig. 2; comparison between the traditional and topological description of palmar and sole patterns, is presented in Fig. 3, and a description of complex patterns on the palm and the sole is shown in Fig. 4. More detailed explanation of the topological method of classification has been presented elsewhere [27, 28]. The main advantage of the new method in genetical studies is that it diminishes the number of possible combinations of pattern elements; on the other hand, it enables the characters, classified by this method, to be expressed in a quantitative form for the purpose of correlational analysis, and, at the same time, in a form, suitable for the computer. Results of correlational analysis, presented here, included: a) intercorrelations between pattern elements on palms and soles, b) cross-correlations between pattern elements of palms and soles and c) familial correlations of selected dermatoglyphic characters on palms and soles. The methods of genetical analysis, applied here, have been explained elsewhere [13,115]. The material for the present study consisted of palm and finger-prints of 414 families (1902 individuals) and of sole prints of 189 families (728 individuals), all of Polish origin. Mean number of children per family was 2.9. The results of correlations between loops and triradii are schematically presented in Fig. 5; the results have revealed those triradii which are complementary to the respective loops. The results of intercorrelations between palmar (a) and sole (b) loops are presented in Table 1 (sexes combined); cross-correlations between pattern elements of palms and soles are illustrated in Fig. 6. The results have shown that there is a considerable variety of loops and triradii with regard to their interrelations with the other loops or triradii on palms and soles. Table 2 presents the results of cross-correlations between combined loops of palms and soles which indicate the interrelationship between the distal loops of palms and soles and between the proximal loops of palms and soles. The results of family correlations for dermatoglyphic pattern elements are presented in Table 3 — for palms and finger-tips and in Table 4 — for soles. In Table 5 — the values of heritability index (h2), dominance-recessivity index (dr)2 and total sex influence (X and Y) indices are given. They all indicate a considerable differentiation of topologically significant pattern elements in respect of heritability, sole characters having, on the whole, lower heritability indices than those of palms and finger-tips. It had been shown previously (15) that, as illustrated in Fig. 7, the characters with low heritability tend, on the whole, to be more intercorrelated than those with relatively higher heritability (only significant correlations are indicated). Mode of inheritance was estimated on the basis of (dr)2 index, considering a frequency of the character tested, using the method, as previously explained (13). A possible mode of inheritance of selected characters is shown in Fig. 8. Some loops (blank) have not been suitable for testing the mode of inheritance because of their low heritability. Some dominance has been detected for the most of characters studied, such as I and Ir and IV palmar loops and the t triradius, and for I and V̂ sole loops, and some recessivity — only for the palmar loop II. Loops III, H on palms and the sum of the ulnar loops on finger-tips seem to occupy an intermediate position. However, these results should be considered approximate, considering also the high values of standard errors — as shown in Table 6. In the comments, the difficulties in the interpretation of the results of genetical analysis are pointed out and a possible relationship of the heritability with the position of a given pattern, the time of its formation in foetal life and some other factors, is postulated. It has also been suggested that, although the inheritance of the majority of characters studied is probably polygenic, it cannot be excluded that a few characters on palms and soles may be determined by single loci on account of both, high heritability and dominance-recessivity indices, and lack of the anatomical relationship with the other loops.